2016
DOI: 10.1140/epjc/s10052-016-4378-0
|View full text |Cite
|
Sign up to set email alerts
|

$$\bar{B}_{d,s} \rightarrow D^{*}_{d,s} V$$ B ¯ d , s → D d , s ∗ V and $$\bar{B}_{d,s}^* \rightarrow D_{d,s} V$$ B ¯ d , s ∗ → D d , s V decays in QCD factorization and possible puzzles

Abstract: Motivated by the rapid development of heavyflavor experiments, phenomenological studies of nonleptonic and are in the scope of Belle-II and LHCb experiments. Moreover, they also provide a way to crosscheck the possible puzzles mentioned above through the similar ratios R V ds and R V / ν . More refined experimental measurements and theoretical efforts are required to confirm or refute such two anomalies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
572
0
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(612 citation statements)
references
References 75 publications
19
572
0
21
Order By: Relevance
“…To compare their thermal conductivities with ones of other 2D materials, the room-temperature thermal conductivity is converted into thermal sheet conductance 46 , and the corresponding value is 14.2 WK −1 and 12.6 WK −1 , respectively. Their thermal sheet conductances are lower than one of semiconducting transition-metal dichalcogenide, group IV-VI, group-VA and group-IV (expect germanene) monolayers 24,46,50 . The very low thermal sheet conductance suggests that SbTeI and BiTeI monolayers are potential 2D thermoelectric materials.…”
Section: Main Calculated Results and Analysismentioning
confidence: 90%
“…To compare their thermal conductivities with ones of other 2D materials, the room-temperature thermal conductivity is converted into thermal sheet conductance 46 , and the corresponding value is 14.2 WK −1 and 12.6 WK −1 , respectively. Their thermal sheet conductances are lower than one of semiconducting transition-metal dichalcogenide, group IV-VI, group-VA and group-IV (expect germanene) monolayers 24,46,50 . The very low thermal sheet conductance suggests that SbTeI and BiTeI monolayers are potential 2D thermoelectric materials.…”
Section: Main Calculated Results and Analysismentioning
confidence: 90%
“…Although such a kind of dataset are starting to be available (see, e.g., [34] from CFHTLenS, and [36] from DES Science Verification data), the survey area is still too small to allow for reducing the statistical uncertainty to an acceptable level and prevent from cosmic variance effects. Moreover, noiseless convergence maps are also needed in order to validate Eq.…”
Section: Moments From Simulated Mapsmentioning
confidence: 99%
“…[14] In that study,predominant I À motion is reported, in agreement with recent modeling results [21,22] and experimental observations. [23][24][25][26][27] In parallel, dominant ion conduction through methylammonium (MA) ions has been claimed in anumber of other contributions. [28][29][30][31] Some reports even state the possibility of both ions being mobile.…”
mentioning
confidence: 99%